Konsep Pendidikan Profetik pada Kepribadian Guru di Era Revolusi Industri 5.0 - Aisyah Nurwulan Ekadiarsi; Amelia Hastiani; Anastasia Clorenza; Andaru Retno Kuncoro; Annisa Laras Khairani (STAI Terpadu Yogyakarta, 2024)
This research uses the literature study method by collecting data from writings (literacy) that have a connection with the topic discussed, namely Islamic Education in the era of the industrial revolution 5.0 This research aims to describe how the concept of prophetic education on the teacher's personality in the era of the industrial revolution 5.0. Prophetic education is a process in which prophetic values such as sincerity, honesty, consistency, justice, and humility are instilled in humans. Through learning that focuses on moral values, learners learn to identify the difference between good and bad values, hoping to improve their quality of life. The prophetic concept in teacher personality becomes a relevant and significant aspect that is expected to provide a holistic, moral, and spiritual view in guiding learners. The results of this study show that if educators can practice the exemplary qualities of the Prophet in learning activities and in everyday life, education in Indonesia will be more qualified, moral, and competent.